Respostas agudas de leucócitos, dano muscular, marcadores de estresse e estado redox em humanos submetidos ao treinamento funcional de alta intensidade - Gomes, João Henrique (2021)
High-intensity functional training (HIFT) programs have become increasingly popular, with a significant increase in the number of practitioners, being designed to improve body composition, anaerobic capacity and cardiovascular fitness. However, the scientific literature lacks information about changes in acute physiological and immunological responses to HIFT and how they can occur, and whether these responses are different according to level of experience and sex. Therefore, the objective of this thesis was to analyze the acute responses of the “Cindy” protocol, as part of a CrossFit® training session, on the immune system, muscle damage, stress markers and the redox status of its practitioners. Specifically, the hypotheses tested were as follows: a single ‘Cindy’ workout session would induce perturbations in immune parameters after a training session, and and less experienced practitioners would be more susceptible to these changes when compared to more experienced practitioners, in the same way women when compared to men. In the current study, twenty-three adult practitioners (31.0 ± 1.0 years) of CrossFit® underwent a single training session (“Cindy” protocol). Subgroup analysis was carried out, being: novices (n = 10) x experienced (n = 13); men (n = 12) x women (n = 11). All protocols used in the present study were approved by the Research Ethics Committee of Federal University of Sergipe and the study was registered with ReBEC. Blood samples were evaluated for lactate, cortisol, creatine kinase (CK), total and differential leukocyte count, thiobarbituric acid reactive substances (TBARS); ferric reducing antioxidant power (FRAP), glutathione peroxidase (GPX); superoxide dismutase (SOD). These variables were assessed before (pre-ex), immediately after (post-ex), 30 minutes (post-30min) and 24 hours after (post-24h) exercise. The number of rounds differed only in the comparison between levels of experience, being similar between sexes. The physiological and perceptual responses to the “Cindy” training did not differ statistically between the groups. For the 23 subjects, the leukocyte count was higher in the post-ex (6.8 to 11.8x103/μL) and returned to baseline values after 30 minutes (p<0.01). The levels of neutrophils (3.3 to 4.5x103/μL) and lymphocytes (2.8 to 5.9x103 / μL) were higher post-ex and returned to baseline values after 24 h, but a decrease in lymphocytes (2.2x103 / μL) was observed after 30 min (p<0.01). CK increased in the post-ex (174.9 a 226.7 U.L-1) and remained elevated until 24 h. The responses of cortisol (14.7 to 17.0 μg/dL) and lactate (1.9 to 13.5 mmol.l-1) increased in the post-ex, but only the lactate level was reduced after 30 min (4.7 mmol.l-1). As for the antioxidant activity, FRAP (84.09 to 106.27 mM ferrous sulfate/mL) and GPX (38.16 to 43.72 μg/Hb) increased, while the SOD enzyme decreased in the post-30min (3286.18 to 2691.58 μg/Hb) for all participants. There is no difference in TBARS at post-30min. One single HIFT session elicited significant acute perturbations in WBC count, stress markers, and muscle tissue, similarly to other high-intensity training regimens of the kind. It is noteworthy that the experienced participants showed greater lymphocyte and cortisol responses than the novice ones did. A small number of variables presented more intense alterations in men than in women. These results revealed that this protocol, in the conditions it was carried out and evaluated, is reliable and can be used equally for novice, experienced, men and women practitioners.